A cost-effectiveness analysis of the use of safety-engineered syringes in reducing HBV, HCV, and HIV burden in Egypt. (1st February 2019) - Mostafa, Aya; Elsisi, Gihan Hamdy
ABSTRACT: Introduction : The objective of this study was to estimate the effects and costs of safety-engineered syringes (SS) as a prevention strategy from HBV, HCV, and HIV infections versus conventional syringes (CS). Methods : A decision-analytic model with five health states was constructed. The clinical parameters and utilities were derived using published data. Direct medical costs from the health care system perspective were sourced from national data. All costs and effects were discounted at 3.5% annually. Results : The estimate of total quality adjusted life years (QALYs) while using SS were 10.87 compared to 9.20 for the use of CS in the Egyptian population exposed to unsafe injection practices. The total costs for using SS and CS were EGP2, 870 and EGP81, 794 (I1, 130 and I32, 202), respectively, per 5.9 injections per person per year. Adopting SS resulted in better outcomes (difference; 1.66 QALYs) and total savings (EGP-78, 924/I-31, 073) per person. Conclusion : Introducing SS in the Egyptian health care system might help in preventing transmission of blood-borne infections that are acquired through health care settings. The overall benefit of investing in this technology is far more than CS. These findings encourage the urgent adoption of SS by health care delivery institutions in similar resource-limited settings.